2020
DOI: 10.3390/jcm9020327
|View full text |Cite
|
Sign up to set email alerts
|

Male Infertility: Shining a Light on Lipids and Lipid-Modulating Enzymes in the Male Germline

Abstract: Despite the prevalence of male factor infertility, most cases are defined as idiopathic, thus limiting treatment options and driving increased rates of recourse to assisted reproductive technologies (ARTs). Regrettably, our current armory of ARTs does not constitute therapeutic treatments for male infertility, thus highlighting an urgent need for novel intervention strategies. In our attempts to fill this void, we have come to appreciate that the production of pathological levels of oxygen radicals within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 193 publications
(246 reference statements)
0
15
0
Order By: Relevance
“…Having established the principles by which to robustly elicit lipid peroxidation in human spermatozoa using AA and the involvement of phospholipase enzymes in this pathway, we next elected to examine the specific involvement of key PUFA substrates in evoking this response. The rationale for this study rests with independent evidence that the lipoxygenase-lipid peroxidation pathway is specifically linked to the metabolism of PUFAs, as opposed to other saturated fatty acids or neutral lipids [ 40 , 41 ]. Furthermore, the balance of evidence indicates that the catalytic activity of ALOX15 in somatic cells is allied to a specific subset of PUFAs, namely AA, LA and DHA, which are all present in human sperm cell membranes [ 27 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Having established the principles by which to robustly elicit lipid peroxidation in human spermatozoa using AA and the involvement of phospholipase enzymes in this pathway, we next elected to examine the specific involvement of key PUFA substrates in evoking this response. The rationale for this study rests with independent evidence that the lipoxygenase-lipid peroxidation pathway is specifically linked to the metabolism of PUFAs, as opposed to other saturated fatty acids or neutral lipids [ 40 , 41 ]. Furthermore, the balance of evidence indicates that the catalytic activity of ALOX15 in somatic cells is allied to a specific subset of PUFAs, namely AA, LA and DHA, which are all present in human sperm cell membranes [ 27 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in the lipid profile was indeed previously associated with sperm dysfunction resulting in infertility and previous studies already identified some of the lipids mainly involved [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the excess production of ROS and RNS are able to induce irreversible modifications to biologically fundamental macromolecules of spermatozoa, such as lipids, proteins and nucleic acids, it has been found that oxidative/nitrosative stress provokes defects in sperm functions by decreasing their motility and fertilizing capacity. In particular, it has been demonstrated that increased levels of ROS and RNS stimulate lipid peroxidation of polyunsaturated fatty acid-rich plasma membranes of spermatozoa [ 58 , 59 , 60 ] and DNA fragmentation [ 61 , 62 , 63 ]. Furthermore, as well as in other pathological conditions such as neurodegenerative diseases, ischemia and cancer [ 64 , 65 , 66 , 67 ], the insurgence of oxidative/nitrosative stress in spermatozoa is associated with mitochondrial dysfunction.…”
Section: Male Infertility and Oxidative/nitrosative Stress: A Ratimentioning
confidence: 99%